Recomendações para o tratamento farmacológico da DPOC: Perguntas e respostas - Fernandes, Frederico Leon Arrabal; Cukier, Alberto; Camelier, Aquiles Assunção; Fritscher, Carlos Cezar; da Costa, Cląudia Henrique; Pereira, Eanes Delgado Barros; Godoy, Irma [UNESP]; Cançado, José Eduardo Delfini; Romaldini, José Gustavo; Chatkin, Jose Miguel; Jardim, José Roberto; Rabahi, Marcelo Fouad; et al. (FapUNIFESP (SciELO), 2017)
The treatment of COPD has become increasingly effective. Measures that range from behavioral changes, reduction in exposure to risk factors, education about the disease and its course, rehabilitation, oxygen therapy, management of comorbidities, and surgical and pharmacological treatments to end-of-life care allow health professionals to provide a personalized and effective therapy. The pharmacological treatment of COPD is one of the cornerstones of COPD management, and there have been many advances in this area in recent years. Given the greater availability of drugs and therapeutic combinations, it has become increasingly challenging to know the indications for, limitations of, and potential risks and benefits of each treatment modality. In order to critically evaluate recent evidence and systematize the major questions regarding the pharmacological treatment of COPD, 24 specialists from all over Brazil gathered to develop the present recommendations. A visual guide was developed for the classification and treatment of COPD, both of which were adapted to fit the situation in Brazil. Ten questions were selected on the basis of their relevance in clinical practice. They address the classification, definitions, treatment, and evidence available for each drug or drug combination. Each question was answered by two specialists, and then the answers were consolidated in two phases: review and consensus by all participants. The questions answered are practical questions and help select from among the many options the best treatment for each patient and his/her peculiarities.
Recommendations for the pharmacological treatment of COPD: Questions and answers
Keywords: Chronic obstructive/drug therapy; Chronic obstructive/prevention & control; Chronic obstructive/therapy; Pulmonary disease